Composite material on the aircraft structure / Ahmad Fadzli Mohd Kamil, Azmi Mohd Nazran and Shahrizal Izzat Mohd Sani - Mohd Kamil, Ahmad Fadzli; Mohd Nazran, Azmi; Mohd Sani, Shahrizal Izzat (Faculty of Mechanical Engineering, 2002)
The main objective of this project is to learn how to manage a project starting from the generation of ideas until the materialization of them. We choose this project of “Composite Material On The Aircraft Structure” because it relevant with our course. It allows us to apply what we have learned in some course like Strength of Material, Aircraft Structure and Metallurgy. We also can be exposed to the industrial field when we meet people during our research. Beside that, we want to learn more and to identify the important properties about composite that make it be a material which can develop the aircraft technology. Lastly, the objective is to prove that composite material can be applied to aircraft structure by testing.